2017
DOI: 10.1073/pnas.1621047114
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial aging as a T-cell–mediated phenomenon

Abstract: In recent years, the myocardium has been rediscovered under the lenses of immunology, and lymphocytes have been implicated in the pathogenesis of cardiomyopathies with different etiologies. Aging is an important risk factor for heart diseases, and it also has impact on the immune system. Thus, we sought to determine whether immunological activity would influence myocardial structure and function in elderly mice. Morphological, functional, and molecular analyses revealed that the age-related myocardial impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 62 publications
7
117
1
Order By: Relevance
“…Interestingly, our data show that pharmacological induction of AMPK that enhanced the autophagy improves contractile responses in aged murine cardiomyocytes challenged with LPS. A new published study showed that myocardial aging is a T-cell-mediated phenomenon that heart-directed immune responses may spontaneously arise in the elderly [23]. Improvement of LPS-induced mitochondrial dysfunction by fasudil was attributed to inhibition of ROCK-dependent Drp1 phosphorylation and activation of autophagic processes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data show that pharmacological induction of AMPK that enhanced the autophagy improves contractile responses in aged murine cardiomyocytes challenged with LPS. A new published study showed that myocardial aging is a T-cell-mediated phenomenon that heart-directed immune responses may spontaneously arise in the elderly [23]. Improvement of LPS-induced mitochondrial dysfunction by fasudil was attributed to inhibition of ROCK-dependent Drp1 phosphorylation and activation of autophagic processes [24].…”
Section: Discussionmentioning
confidence: 99%
“…1F), suggesting that chronic TLR2 deficiency causes contractile dysfunction in male mice. These overall changes closely resemble the cardiac structure and function of aged mice, which exhibited increased left ventricular dimension, decreased wall thickness, and decreased fractional shortening (34,35). To check whether the development of adverse remodelling and cardiac dysfunction is gender dependent, we analysed the cardiac structure and function of 8-month-old wild type and TLR2-KO female mice.…”
Section: Tlr2 Deficient Mice Develop Spontaneous Gender Independentmentioning
confidence: 91%
“…Age-dependent decline in the number of macrophages has been observed in aging hearts (35,43). Therefore, we tested whether TLR2-KO hearts showed any changes in the population of macrophages in the heart.…”
Section: Tlr2 Deficient Hearts Harbour Reduced Residual Macrophages Amentioning
confidence: 99%
“…Since the first description of inflammatory mediators in HF patients in 1990, the links between inflammation and HF have become an extensive subject of study. This applies to HF caused by different pathological conditions, ranging from ischemic injury, to pressure‐overload, or even low‐grade chronic stress . The details of what triggers the inflammatory response in HF are still not precisely deciphered, though among the possible causes one could list the mechanical stress that cardiomyocytes undergo during blood pressure overload, as well as the associated hypoxia and reactive oxygen species (ROS) generation; it is thought that this may induce the production of proinflammatory cytokines by the ailing myocardium .…”
Section: Introduction To Cardiac Hypertrophymentioning
confidence: 99%
“…This applies to HF caused by different pathological conditions, ranging from ischemic injury, 11 to pressure-overload, 12 or even low-grade chronic stress. 13 The details of what triggers the inflammatory response in HF are still not precisely deciphered, though among the possible causes one could list the mechanical stress that cardiomyocytes undergo during blood pressure overload, as well as the associated hypoxia and reactive oxygen species (ROS) generation; it is thought that this may induce the production of proinflammatory cytokines by the ailing myocardium. 9,14 The inflammatory response that occurs after cardiac injury is generally characterized by three phases: (1) production of inflammatory mediators (cytokines and chemokines), (2) recruitment of immune cells that intervene in the tissue remodeling process, (3) production of anti-inflammatory mediators that down-regulate the inflammatory response.…”
Section: Introduction To Cardiac Hypertrophymentioning
confidence: 99%